Comparison of Two Manual Therapy Techniques in Patients with Carpal Tunnel Syndrome: A Randomized Clinical Trial - Ghadam Ali Talebi; Payam Saadat; Yahya Javadian; Mohammad Taghipour (Babol University of Medical Sciences, 2020)
Background: Manual therapy techniques are part of physiotherapy treatment of carpal tunnel syndrome (CTS) which are classified into two groups including nerve mobilization and mechanical interface mobilization. The aim of the study was to find which manual therapy method-technique directed to mechanical interface and nerve mobilization-has superior beneficial effects on clinical and electrophysiological findings in conservative management of patients with CTS. Methods: Thirty patients with CTS participated into two groups namely: mechanical interface and nerve mobilization in this randomized clinical trial. The intervention was performed three times weekly for 4 weeks. Mechanical interface mobilization was directed to structures around the median nerve at the forearm and wrist. Techniques of median nerve gliding and tension were used in the nerve mobilization group. The outcome measures included visual analogue scale (VAS), symptom severity scale (SSS), hand functional status scale (FSS) and motor and sensory distal latencies of median nerve. Paired t-test and ANCOVA were used for statistical analysis. Results: At the end of the 4th week of the treatment, the mean of VAS, SSS and FSS significantly improved in both groups (p<0.05), but the difference was not significant between the two groups (P>0.05). Although the mean of motor and sensory distal latencies of median nerve at the end of the treatment period only improved in the nerve mobilization group (p<0.05), the difference was not significant between the two groups (P>0.05). Conclusion: Mechanical interface mobilization and nerve mobilization techniques are not superior to each other in reducing pain and improving hand symptoms and functional status.